An introduction to operating systems - Deitel, Harvey M., 1945- (Reading, Mass. : Addison-Wesley Pub. Co., 1989)
The third edition of Operating Systems has been entirely updated to reflect current core operating system concepts and design considerations. To complement the discussion of operating system concepts, the book features two in-depth case studies on Linux and Windows XP. The case studies follow the outline of the book, so readers working through the chapter material can refer to each case study to see how a particular topic is handled in either Linux or Windows XP. Using Java code to illustrate key points, Operating Systems introduces processes, concurrent programming, deadlock and indefinite postponement, mutual exclusion, physical and virtual memory, file systems, disk performance, distributed systems, security and more. New to this edition are a chapter on multithreading and extensive treatments of distributed computing, multiprocessing, performance, and computer security. An ideal up-to-date book for beginner operating systems readers.
Includes bibliographical references and index.
Keywords: Operating systems (Computers); Computing